Knowledge integration and organisational performance of data analytics in the family business - Ismael Barros-Contreras; Manuel Morales-Serazzi; Angel Torres-Toukoumidis; Jesús Manuel Palma-Ruiz (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study addressed the connection between the organisational performance of data analytics and the elements that contribute to knowledge integration (KI) in family businesses under the scope of the knowledge-based view theory. The conceptual model was validated based on the responses of 135 directors of Chilean family firms by using a partial least squares-structural equation modeling (PLS-SEM) methodology. The results show a relationship between the three components of KI and their impact on the organisational performance of data analytics, in addition to the moderating effects of both the quality of information and the information alignment within the proposed model. Our findings contribute data analytics to the family business literature and support organisational management by encouraging cooperation and the sharing of information and expertise among family members.
Keywords: 650; data analytics; family business; knowledge integration; organisational performance